Roles and Problems of Stroke Caregivers: A Qualitative Study in Yogyakarta, Indonesia - Vidyanti, Amelia Nur; Muhrodji, Paryono; Wicaksono, Hendrawan Dian Agung; Satiti, Sekar; Trisnantoro, Laksono; Setyopranoto, Ismail (F1000 Research Ltd, 2022)
Background: Caregivers play a central role in post-stroke patients' care. However, the role of and problems managed by caregivers have not been widely studied, particularly in Indonesia. This study aims to explore the roles and problems of caregivers in post- stroke patients’ care. Method: This was a qualitative study. Seven caregivers of post-stroke patients from the homecare clinic of Dr Sardjito General Hospital were purposely selected during January 2017 to June 2018. Focus group discussions were conducted to explore the roles and problems of caregiving. Results: Themes related to caregivers’ roles were: connecting patients with medical personnel and other family members, maintaining patients’ health conditions by fulfilling basic needs and assisting rehabilitation, as well as maintaining patients’ psychological conditions by encouraging conversation, telling jokes, or recreation. On the other hand, themes related to caregivers’ problems were: lack of knowledge caused by education inadequacy, underappreciated and unconcerned family, suboptimal service including limited physiotherapy and pharmacy resource, unthorough administration, lack of communication, physical limitations, and burnout, as well as uncooperative patients. Conclusions: Caregivers play essential roles as communicators and help to maintain patient's health conditions. Common problems are related to a lack of knowledge about strokes and a lack of attention from family. Further research to study the effects of these findings on the quality of life of both patient and their caregiver, as well as how to handle the caregiver issues should be investigated.